2015
DOI: 10.1001/jamaoncol.2015.3151
|View full text |Cite|
|
Sign up to set email alerts
|

Risk Adjusting Survival Outcomes in Hospitals That Treat Patients With Cancer Without Information on Cancer Stage

Abstract: Importance Instituting widespread measurement of outcomes for cancer hospitals using administrative data is difficult due to the lack of cancer specific information such as disease stage. Objective To evaluate the performance of hospitals that treat cancer patients using Medicare data for outcome ascertainment and risk adjustment, and to assess whether hospital rankings based on these measures are influenced by the addition of cancer-specific information. Design Risk adjusted cumulative mortality of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 21 publications
1
97
0
2
Order By: Relevance
“…Recent research has suggested that the designation may also serve as a benchmark to assess the quality of cancer care. 10,11,22,23 …”
Section: Discussionmentioning
confidence: 99%
“…Recent research has suggested that the designation may also serve as a benchmark to assess the quality of cancer care. 10,11,22,23 …”
Section: Discussionmentioning
confidence: 99%
“…Within the United States, risk-adjusted mortality overall among cancer patients is lowest at cancer specialty hospitals and highest at community hospitals. [34] Among National Cancer Institute (NCI) designated cancer centers, a subset of the oldest cancer hospitals had the lowest risk of death.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown that high-volume hospitals, high physician volume, and specialization are associated with better cancer outcomes [4,5]. A recent study reported that, across all cancer types, the 1-year mortality rate in specialty care hospitals was 10% lower than in community hospitals, and this pattern remained consistent for up to 5 years [6]. However, specialty care hospitals commonly treat a heterogeneous group of patients where some patients may receive their initial treatment within these specialty care hospitals and others may initiate their treatment in community hospitals and eventually establish follow-up care in the specialty care hospital.…”
Section: Introductionmentioning
confidence: 99%